ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2015) - Utami, Putri Setyo; Meiranto, Wahyu (Diponegoro Journal of Accounting, 2017)
This study aims to analyze the factors that affect earnings management which is measured by discretionary accruals. These factors include dividend payment, leverage, audit independence, and free cash flow. The control variables that used in this research are profitability and size of firm. The population of this study are manufacturing companies listed on the Indonesia StockExchange (BEI) in 2013-2015. Total sample of this research for three years are 111 companies that selected through purposive sampling method. Research data were analyzed using multiple regression analysis. The results showed that two independent variables namely leverage and free cash flow have a significant negative effect on earnings management. While dividend payment and audit independence have no significant effect on earnings management. Then for both control variables have a significant effect. Profitability has a positive effect while the size of firm has a negative effect on earnings management.